BROADCASTING OF URBAN-STATISTICS VIA VEHICULAR INTELLECT DIA (International Journal of Engineering and Computer Science, 2017)
We present the boomerang protocol to efficiently retain information at a particular geographic location in a sparse network of highly mobile nodes without using infrastructure networks. To retain information around certain physical location, each mobile device passing that location will carry the information for a short while. This approach can become challenging for remote locations around which only few nodes pass by. To address this challenge, the boomerang protocol, similar to delay-tolerant communication, first allows a mobile node to carry packets away from their location of origin and periodically returns them to the anchor location. A unique feature of this protocol is that it records the geographical trajectory while moving away from the origin and exploits the recorded trajectory to optimize the return path. Simulations using automotive traffic traces for a southern New Jersey region show that the boomerang protocol improves packet return rate by 70 percent compared to a baseline shortest path routing protocol. This performance gain can become even more significant when the road map is less connected. Finally, we look at adaptive protocols that can return information within specified time limits. Index Terms—Geocache, GPS, mobile, location-aware information, infrastructureless data management.